2021
DOI: 10.1109/access.2021.3079119
|View full text |Cite
|
Sign up to set email alerts
|

An Improved SFLA-Kmeans Algorithm Based on Approximate Backbone and Its Application in Retinal Fundus Image

Abstract: In order to improve the global search ability of K-means algorithm and the clustering effect, a K-means method based on the approximate backbone and the shuffled frog leaping algorithm was proposed. Firstly, the classic iterative formula of the K-means algorithm is replaced by the classic shuffled frog leaping algorithm to obtain better clustering results. Secondly, the K-means algorithm based on the approximate backbone and the shuffled frog leaping algorithm is used for the obtained clustering results. Inste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…Finally, by appealing to all the experimental results, it can be found that MOLNMGWO is an algorithm with excellent competitive ability, which can be applied in an extensive range of fields. For example, disassembly process planning (Hsu and Wang 2021), inversion analysis of seepage parameters of earth dams (Xu amd Li 2021), medical image processing problem (Ding et al 2021), distributed flexible job shop scheduling problem (Meng et al 2020), economic dispatch (Cai et al 2007), network reconfiguration (Assadian et al 2010), urban siting problem of electric vehicle charging piles (Awasthi et al 2017), and a series of other advanced fields.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, by appealing to all the experimental results, it can be found that MOLNMGWO is an algorithm with excellent competitive ability, which can be applied in an extensive range of fields. For example, disassembly process planning (Hsu and Wang 2021), inversion analysis of seepage parameters of earth dams (Xu amd Li 2021), medical image processing problem (Ding et al 2021), distributed flexible job shop scheduling problem (Meng et al 2020), economic dispatch (Cai et al 2007), network reconfiguration (Assadian et al 2010), urban siting problem of electric vehicle charging piles (Awasthi et al 2017), and a series of other advanced fields.…”
Section: Discussionmentioning
confidence: 99%
“…Algoritma K-Means adalah salah satu algoritma dengan teknik clustering berdasarkan pembagian jarak dalam data mining. Keuntungan menggunakan algoritma ini mudah dipahami, diterapkan, serta memiliki efek pengelompokan yang baik sehingga K-Means banyak digunakan dalam bidang penelitian [8]. Namun, algoritma ini juga memiliki kekurangan, yakni memiliki ketergantungan yang kuat pada pemilihan pusat cluster awal [9].…”
Section: Pendahuluanunclassified
“…Ding et al 117 suggested a K‐means approach based on the approximation backbone and the SFL algorithm to increase the global exploration ability of the K‐means technique and the clustering impact. To enhance clustering results, the traditional iterative procedure of the K‐means clustering was substituted with the standard shuffling frog leaping algorithm (CSFLA).…”
Section: Optimization Algorithms For Disease Identificationmentioning
confidence: 99%